Single-Session Dance/Movement Therapy for People with Acute Schizophrenia: Development of a Treatment Protocol. - Biondo, Jacelyn; Gerber, Nancy (American Journal of Dance Therapy, 2020)
People experiencing acute symptomatology associated with schizophrenia require interventions that support stabilization. Dance/movement therapy (DMT) can be a promising treatment option for this population due to the potential for verbal communication difficulties, alternative reality bases, and movement dysfunctions associated with schizophrenia. However, due to the improvisational nature of DMT, it is often difficult to identify the specific interventions or components of the therapeutic process that may support stabilization and symptom reduction. Moreover, as inpatient lengths of stay decrease, it is imperative that we implement shorter treatment protocols. This inquiry analyzed 14 single-session DMT group sessions for people with acute schizophrenia on an inpatient psychiatric unit to determine the components of the DMT process common amongst each session. Data analysis of therapist field notes informed the development of a single-session DMT treatment protocol to outline the four phases of a single-session DMT group: warm-up, thematic development, cool down, and verbal discussion. Results of this inquiry determined that there were repeated components of the 14 sessions. A systematic content analysis of the therapy process is potentially useful for the examination of what may specifically contribute to symptom reduction in DMT groups.